1984
DOI: 10.1152/ajpcell.1984.246.3.c347
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-specific receptor-mediated slowing of beat rate in embryonic heart cells

Abstract: Spheroidal aggregates of embryonic heart cells showed their spontaneous beat rate when exposed to insulin. The concentration that produced a half-maximal response (1.7 nM) corresponded to the dissociation constant of binding to a specific high-affinity insulin receptor. The pace-maker phase of action potentials recorded during insulin perfusion was preceded by a prolonged or flattened after hyperpolarization, and its slope was less steep than controls. The action potential duration was also prolonged. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In embryonic chick heart cells, insulin causes a ouabain-insensitive hyperpolarization and increases a timeindependent background outwad cunent (Fischmeister ea al. 1983;DeHaan et al 1984). In mammalian myocardium (canine false tendons a d papillary muscle from rats and kittens) the hyperpalmizing effect of insulin is enhanced by Cs ions and prevented by cooling, pretreatment with cardiac glycosides, and previous exposure to hypoxic substrate-free medium (40-45 'Author to whom all correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In embryonic chick heart cells, insulin causes a ouabain-insensitive hyperpolarization and increases a timeindependent background outwad cunent (Fischmeister ea al. 1983;DeHaan et al 1984). In mammalian myocardium (canine false tendons a d papillary muscle from rats and kittens) the hyperpalmizing effect of insulin is enhanced by Cs ions and prevented by cooling, pretreatment with cardiac glycosides, and previous exposure to hypoxic substrate-free medium (40-45 'Author to whom all correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Time constants for decay were fitted by a modified Levenberg-Marquardt least-squares minimization algorithm (Dempster, 1993) (Freestone et al 1995). Vetter et al (1988) have also reported an increase in cardiac contractility in neonatal rat cardiac myocytes in culture due to these two agonists, whilst DeHaan et al (1984) have described a negative chronotropic effect of insulin on embryonic rat cardiac myocytes in culture. The chronotropic action of IGF-1 on cardiac cells has not been as well delineated, however.…”
mentioning
confidence: 99%